Game AI pro 360. Guide to character behavior - Rabin, Steve (Boca Raton : CRC Press, 2020)
"Cutting-edge character behavior techiques for game AI primarily from game developers of shipped commercial games. The book acts as a toolbox of techniques that can be applied to many common and not-so-common situations"--
OCLC-licensed vendor bibliographic record.
Keywords: Computer games -- Programming; Computer games -- Authorship; Artificial intelligence; Video game characters; COMPUTERS / General; COMPUTERS / Computer Graphics / Game Programming & Design